Unreal engine 5. (Packt Publishing, 2022)
Create vehicles using 100% blueprints and ready-to-use Unreal Engine 5 assets from scratch in just a few hours. This is a very practical course aiming to create functional vehicles in a limited time. About This Video Create complete AAA game vehicles in Unreal Engine with the help of blueprints from scratch No matter in what field you are games or films, you will be able to create an exact replica of a functional vehicle Create a mini-game with checkpoints and best lap time along with adding best-games features In Detail Unreal Engine is the world's most open and advanced real-time 3D creation tool for photoreal visuals and immersive experiences. Unreal Engine is a complete suite of creation tools for game development, architectural and automotive visualization, linear film and television content creation, broadcast and live event production, training and simulation, and other real-time applications. This course will cover in detail topics on how to create AAA vehicle in Unreal Engine 5. Starting with the basic setup of the vehicle, we will be using the free Matrix demo scene to kickstart our environment. Then you will add car engine sounds, edit the environment and customize our car, and add logic to our speed meter to work with the car. Following that, you will add friction to your car, set up the car engine, and create and tweak the car's suspension and steering. Next, you will be tweaking and fine-tuning car stats. After that, you will be adding car impact, skidding sound, and creating a particle system for tire smoke. Finally, you will be creating checkpoint logic, setting up timers, and testing our game demo. By the end of this course, you will be confident enough to use Unreal Engine to create functional vehicles. You will be able to create a complete 3D vehicle and its environment from scratch with the help of added assets provided. Audience This course is ideal for the Unreal Engine 5 developers looking to create AAA realistic vehicles for their games, Unreal Engine 5 enthusiasts who want to expand their knowledge, and developers who want to know more about how to create realistic vehicles from scratch with Blueprints. You would need a basic to intermediate understanding of blueprints along with the Unreal Engine 5 interface and basic knowledge of the engine. You will need to download the free Matrix demo scene from the Epic Games marketplace to follow along the course.